2012
DOI: 10.1051/0004-6361/201219357
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulations of the interaction between Type Ia supernova ejecta and their main sequence companions

Abstract: Context. The identity of the progenitor systems of Type Ia supernovae (SNe Ia) is still uncertain. In the single-degenerate scenario, the interaction between the supernova blast wave and the outer layers of a main sequence companion star strips off hydrogen-rich material which is then mixed into the ejecta. Strong contamination of the supernova ejecta with stripped material could lead to a conflict with observations of SNe Ia. This constrains the single-degenerate progenitor model. Aims. In this work, our prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
192
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(210 citation statements)
references
References 71 publications
16
192
2
Order By: Relevance
“…Most interestingly, Maguire et al (2016) constrained the removed H-mass in SN 2012cg to be 0.005 − 0.008 M ⊙ , which is much less massive than the removed H-rich mass predicted from recent hydrodynamical simulations for the MS and RG donor scenario ( 0.1 M ⊙ with a typical velocity of 1000 km s −1 , e.g., Liu et al 2012Liu et al , 2013aPan, Ricker & Taam 2012). This poses a serious challenge to the MS/RG donor binary system as the progenitor of SN 2012cg.…”
Section: Searching For Stripped Hydrogenmentioning
confidence: 76%
See 3 more Smart Citations
“…Most interestingly, Maguire et al (2016) constrained the removed H-mass in SN 2012cg to be 0.005 − 0.008 M ⊙ , which is much less massive than the removed H-rich mass predicted from recent hydrodynamical simulations for the MS and RG donor scenario ( 0.1 M ⊙ with a typical velocity of 1000 km s −1 , e.g., Liu et al 2012Liu et al , 2013aPan, Ricker & Taam 2012). This poses a serious challenge to the MS/RG donor binary system as the progenitor of SN 2012cg.…”
Section: Searching For Stripped Hydrogenmentioning
confidence: 76%
“…However, as discussed by Maguire et al (2016), the observed flux at the position of H α was converted to the mass with one-dimensional models by Mattila et al (2005), and Lundqvist et al (2013) who performed spectral synthesis modelling based on the earliest two-dimensional impact simulation of Marietta, Burrows & Fryxell (2000), which might lead to some uncertainties of the results. To place a more stringent constraint on the upper-limit mass for non-detection of swept-up H in latetime spectra of SNe Ia, future multi-dimensional radiative transfer modelling with ejecta structures obtained from updated threedimensional impact simulations such as those of Liu et al (2012) and Pan, Ricker & Taam (2012) is still needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These models can be used in future work to study the impact of the SN Ia explosion on the donor star and thus help predict the expected properties of former companions stars when searching for these in SN Ia remnants (see e.g. Marietta et al 2000;Di Stefano & Kilic 2012;Liu et al 2012;Pan et al 2010Pan et al , 2012Pan et al , 2013. These authors demonstrated that whereas helium star donors may only lose about 5% of their mass, and main-sequence star donors lose some 10-20%, giant star donors may lose most of their envelope because of the SN impact.…”
Section: Sn Ia Progenitor Calculations and Shell Impactmentioning
confidence: 99%